Role of the family in the transition from preschool to elementary school - Padilla Faneytt, Emelinda (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study aims to analyze the perception on the educational transition from preschool to first grade of the parents of Santo Domingo, Dominican Republic. An online self-administered questionnaire was written, which was validated through expert judgment and a pilot study. A high percentage stated that they had not received training on educational transition from the school. They believe that the school is primarily responsible for preparing the family to address the transition. Also, we recognize that the family has a fundamental role in the success of the transition.